2020
DOI: 10.1007/s42729-020-00224-y
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Exclusion Affects Seed Yield and Physiological Traits of Wheat Genotypes Grown Under Salt Stress

Abstract: Increasing salinization is a real threat to food security by diminishing the performance of glycophyte staple crop wheat. To tackle salinity, one option is to identify and use salt-tolerant germplasm but salinity tolerance is a multigenic trait which is conferred by a large array of interacting physiological and biochemical processes. Keeping this in mind, (eighteen) physiological indices were used to appraise salt tolerance of 20 bread wheat genotypes and specifically evaluated the effect of sodium exclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Our results support the hypothesis that the agronomical quality of pepper seeds diminishes with rising salinity of the nutrient solution used for mother plant fertigation. These findings are important because escalating soil and water salinization diminishes crop yields, thus posing a major threat to food security (Saddiq et al 2020;Wang et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Our results support the hypothesis that the agronomical quality of pepper seeds diminishes with rising salinity of the nutrient solution used for mother plant fertigation. These findings are important because escalating soil and water salinization diminishes crop yields, thus posing a major threat to food security (Saddiq et al 2020;Wang et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study also showed that with increase in salinity and dust application in H. aphyllum species, the content of proline increased. Proline plays an essential role in osmotic regulation and reduction of sodium toxicity in plants (Saddiq et al, 2020 ). Proline accumulation has a positive and direct relationship with increased resistance to dehydration under salinity and drought stresses in plants (Saneoka et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results on stress caused due to salinity impact on wheat plants agree with those obtained earlier on sunflower plants ( Abd El-Hameid and Sadak, 2020 ). Salinity stress severely disturbs plant growth via various physiological processes ( Mujeeb-Kazi et al., 2019 ; Saddiq et al., 2019 ; Saddiq et al., 2020 ). Salinity affected wheat growth parameters via decreased water availability and increased levels of Na and Cl ions which interfered with essential macro elements such as Mg, K, and Ca uptake from the soil, thus resulting in nutrient deficiency ( Awad et al., 2012 ; Saddiq et al., 2019 ; Saddiq et al., 2020 ; Mohamed et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%